KNOWLEDGE AND RESPONSIBILITY OF THE PARENTS TOWARD CHILD'S ORAL HEALTH: A CROSS-SECTIONAL STUDY - R, Shasmitha; AK, Shanmugaavel (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of this study was to understand the dental knowledge and responsibility of the parents toward child's oral health in a dental office. Methods: A questionnaire (Annexure A) was distributed to 200 parents who came to Saveetha Dental College and Hospitals. Parent's information regarding dental knowledge, responsibility taking, and knowledge regarding child's oral health was collected with the aid of the structured questionnaire. Result: The results showed that the dental knowledge of parents is lower than that of the experts. Parents mentioned that fluoride has less importance in enamel protection (p=0.87) than the experts (p<0.001). Almost 100% of the parents were engaged in the daily assistance of tooth brushing for their children. However, child's diet control is poor. Nearly 26% of the parents have no control of sweet consumption for their child. About 45% of the parents have no control of biscuits consumption for their child. Moreover, 22% of the parents of uncooperative child dental patients mentioned that it is a dentist's responsibility for the unwillingness of the treatment and treatment refusal stated by the child. Conclusion: This study showed that the parents have poor dental knowledge and are not responsible for their child's oral health. They do not maintain proper dietary habits for their children which may lead to the increased incidence of caries in childhood. Hence, there is a need for increase in dental knowledge of the parents to maintain a proper oral health of their children. Keywords: Parental behavior, Parental dental knowledge, Child's behavior.